Phenotypic plasticity and epithelial‐to‐mesenchymal transition in the behaviour and therapeutic response of oral squamous cell carcinoma. (16th January 2015) - Vig, Navin; Mackenzie, Ian C.; Biddle, Adrian
<x xml:space="preserve">Abstract</x> It is increasingly recognised that phenotypic plasticity, apparently driven by epigenetic mechanisms, plays a key role in tumour behaviour and markedly influences the important processes of therapeutic survival and metastasis. An important source of plasticity in malignancy is epithelial‐to‐mesenchymal transition (EMT), a common epigenetically controlled event that results in transition of malignant cells between different phenotypic states that confer motility and enhance survival. In this review, we discuss the importance of phenotypic plasticity and its contribution to cellular heterogeneity in oral squamous cell carcinoma with emphasis on aspects of drug resistance and EMT.